2010
DOI: 10.1007/s00535-010-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-quenching and anti-apoptotic effect of polaprezinc on indomethacin-induced small intestinal epithelial cell injury

Abstract: The protective effect of PZ on indomethacin-induced small intestinal injury may be dependent on its ROS-quenching effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…Cerebrovascular dysfunction is caused by ROS directly and via tight junction modification and matrix metalloproteinase activation (39). Intracellular ROS accumulates secondary to mitochondrial dysfunction (30,36). We show that DKA-P, but not DKA-CM, elevated intracellular oxidative stress in hCMEC/D3, indicating that DKA-P contains mitochondrial toxic substances exclusive of alterations in the cytokines/chemokines we investigated.…”
Section: Discussionmentioning
confidence: 75%
“…Cerebrovascular dysfunction is caused by ROS directly and via tight junction modification and matrix metalloproteinase activation (39). Intracellular ROS accumulates secondary to mitochondrial dysfunction (30,36). We show that DKA-P, but not DKA-CM, elevated intracellular oxidative stress in hCMEC/D3, indicating that DKA-P contains mitochondrial toxic substances exclusive of alterations in the cytokines/chemokines we investigated.…”
Section: Discussionmentioning
confidence: 75%
“…Our data confirmed that Zn-depleted cells caused an increase in the activation of Caspase 3, in parallel with a higher percentage of apoptotic cells as measured via the CBMN-Cyt assay. Previous literature has shown that ZnC has a strong cytoprotective effect that might be due to the synergistic effect of Zn and L-carnosine (Nishida et al 2010;Omatsu et al 2010). However, there was no difference for the effect of the 2 different Zn forms when 2-way ANOVA analysis was performed.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, in vitro studies using intestinal epithelial cell lines also have indicated that indomethacin induced apoptosis of the intestinal epithelial cells accompanied by an increased production of reactive oxygen species (ROS) (26,27). Omatsu et al (28) have reported that indomethacin induced small intestinal epithelial apoptosis through ROS production and subsequent release of cytochrome c and smac/DIABLO and the activation of caspase-3 in vitro. On the other hand, TNF-α is the prototypical member of a family of cytokines that also include the Fas, CD40 and TNF-related apoptosis inducing ligands, and that induce apoptosis, differentiation, cell activation, and inflammation (29).…”
Section: Discussionmentioning
confidence: 99%